Evaluating RANS and LES turbulence models in hybrid wave modelling of breaking waves - Zhang, Chengzhao; Buldakov, Eugeny (Frontiers in Marine Science, 2025)
Understanding the characteristics of breaking waves in deep and intermediate waters is crucial for air-sea interactions. Recent advancements in modelling these interactions have often relied on numerical wave tanks using Stokes waves, which may not fully represent real-world conditions. To address this gap, we developed a numerical wave tank to investigate the effects of different turbulence models on the performance of our numerical wave model in simulating breaking waves under more realistic wave conditions. A hybrid model that couples a Lagrangian wave model with a VOF model based on OpenFOAM is developed to simulate breaking wave groups resulting from dispersive focussing, with a spectrum related to a modelled sea state. The numerical results obtained through the hybrid wave model without turbulence models are validated against experimental data, demonstrating a high level of accuracy. Then, four turbulence models including RANS standard k − ϵ, RNG k − ϵ models, LES Smagorinsky and LES k-equation turbulence models are applied to the hybrid wave model with peak-focussed wide band Gaussian (GW) spectrum. The effects of turbulence models on the prediction of breaking crests, the energy dissipation due to breakers and the estimation of the breaking strength parameter b are investigated. The findings demonstrate that the turbulence models can significantly affect the numerical results for weak breaking cases. Notably, the hybrid wave model with the LES k-equation turbulence model showed superior performance. This proposed numerical wave tank can be a promising tool for investigating air-sea interactions in 3D simulations under more realistic wave conditions.